Geometry coffee table / Nur Hamizan Suhaimei - Suhaimei, Nur Hamizan (Faculty of Applied Sciences, 2017)
This final year project intends to come out with a new coffee table design that utilizes a combination of materials namely, wood, metal and glass. The study also aims to evaluate customer satisfaction toward the quality of the coffee table design and material used. The purpose of designing this coffee table is to apply the combination of wood, metal and glass to enhance the appearance of a product and determine respondent's satisfaction of the design of the coffee table. The top of the coffee table was constructed with two types of wood: wood disc and wood pallet. While, the leg structure was made from metal and glass in the middle compartment. After the design and manufacturing process, a survey was undertaken in evaluating customer satisfaction on the characteristics of the product. A set of questionnaire was distributed to 100 respondents of different gender, age, resident area and status. The characteristics evaluated by the respondents include design of this coffee table, material, satisfaction, commercialization and price